The Qualiy Of Fresh Mackerel Tuna (Euthynnus Affinis) Catched Using The Purse Seine With Different Methods On The Ship - Sulfiana Sulfiana; Sukmawati Sukmawati; Fatimah Hardianti (Baselang, 2023)
Fisherman generally use purse seine fishing gear to catch mackerel tuna because it is able to effectively catch pelagic fish that behave in large groups, both in coastal and offshore areas. However, until now the problem faced by fishermen and ship owners is the decline in the quality of the fish they catch due to the length of time they catch fish at sea. This study aimed to analyze the effect of different tasting metods and storage duration on the quality of mackerel tuna (Euthynnus affinis). This study used a completely randomized factorial design (RAL) involving 2 factor and each treatment was carried out in 3 replicates. . The treatments used were the fish icing method (bulk, 1-layered fish, and 2-layered fish) with a ratio of ice and fish 1:1 and a storage duration of 12, 24, and 36 hours. Statistical analysis of the quality of mackerel tuna (Euthynnus affinis) wa carried out, namely temperature, organoleptic and coliform. The results showed that after 36 h of storage theter was no difference in organoelptic value, while the temperature and coliform values had different values, namely the stacked methode got result (4,3±0,58) (6,2±0), layered method 1 (4,6±0,58) (6,2±0) and layered method 2 (7,6±0,58) (6,1±1,08). Of the trhree testing methods that were given treatment with different storage times, the result were not much different, but when viewed from the temperature value, the stacking methods is the best method.